Influência do distúrbio mineral e ósseo na ocorrência e progressão da calcificação vascular em pacientes em diálise crônica - Castro, João Henrique [UNESP] (2015)
Cardiovascular disease is the main cause of death in patients with chronic kidney disease (CKD) in hemodialysis and vascular calcification (VC) is common in this population. The main objective of this study was to evaluate the association of markers of mineral and disorder on the presence and progression of VC in a cohort of dialysis patients. Secondarily, it was intended to identify associations between clinical, laboratory and body composition markers with the presence and progression of VC. There were included patients aged over 18 years on chronic dialysis for more than 90 days. The patients were submitted to bone biopsy at the beginning of the follow-up and histomorphometric data analyzed. To investigate VC a sum of radiological scores of Kauppila and Adragão were obtained in two occasions: at the beginning of the follow-up and after 12 months. In addition, clinical, hormonal, inflammatory, biochemical and nutritional evaluation were performed. Results: Sixty patients completed the study; 41.7% were female, 43.4% diabetics, and the average age was 56.7 years (range 25 to 89 years). At the beginning of the follow-up, 75% of the patients showed VC and its progression was observed in 56.8%. At multivariate analysis, age > 60 years (Odds ratio = 50.2, 95% CI=4.1-618.4, p=0.002), FGF23>3000 Ru/mL (Odds ratio = 5.7, 95% CI=1.00-329, p=0.05), and fetuin A>673 g/l (Odds ratio = 7.34, 95% CI=1.26-43.7, p=0.03) were associated with VC. As for the VC progression, the association was shown to age>60 years old (Odds ratio = 4.3, 95% CI=1.003-18.5, p=0.049), fetuin A> 673 g/l (Odds ratio = 6.4, 95% CI = 1.47-27.9, p=0.01), and the non-use of statins (Odds ratio = 5.6, 95% CI=1.13-28.1, p=0.03). It was not possible to show the association with bone turnover markers and the histomorphometric findings both in diagnosis and progression of VC. In conclusion, the present study reinforces the role of aging, the FGF23 level and the statin protection in ...